Performance of Rejuvenated Asphalt and Mixtures with Waste Engine Oil Bottom and Liquid Styrene-Butadiene Rubber - Gang Zhou; Yi Tian; Liang Gong; Zhansheng Pang; Tianquan Chen (Advances in Materials Science and Engineering)
To address the inadequate performance of rejuvenated asphalt when waste engine oil bottom (WEOB) is used as an asphalt rejuvenator, liquid styrene-butadiene rubber (liquid SBR) was used to enhance the performance of WEOB-rejuvenated asphalt. By testing the basic physical properties of asphalt and using the high- and low-temperature rheology, differential scanning calorimetry, Fourier infrared spectroscopy, and atomic force microscopy (AFM) tests, the index and microstructure changes of asphalt before and after aging and regeneration, from macrolevels and microlevels, were studied, along with the high- and low-temperature performance and water stability of the rejuvenated asphalt mixture. The WEOB decreased the glass transition temperature and low-temperature performance grade of aged asphalt and resulted in a significant effect on the recovery of penetration and softening point of aged asphalt; however, the recovery of low-temperature ductility was inadequate. Compared with WEOB, a rejuvenator comprising WEOB and liquid SBR (WEOB-S) further decreased the glass transition and continuous grading temperatures of aged asphalt, improved its low-temperature performance, and significantly influenced its ductility recovery. The AFM test showed that WEOB-S effectively dispersed the agglomerated bee-like wax crystals or macromolecular asphaltene structures in the aged asphalt, decreased the number and crests of the bee-like structures, and improved the microscopic uniformity, thus obtaining better macroscopic physical properties. Both WEOB and WEOB-S improved the low-temperature performance and water stability of rejuvenated asphalt mixtures; however, WEOB-S was more effective.